Mid-Term Outcomes of a Hybrid Approach Involving Open Surgery Plus TEVAR of the Descending Aorta in the Treatment of Complex Type A Dissection - Li, J.; Stadlbauer, A.; Terrazas, A.; Floerchinger, B.; Pfister, K.; Creutzenberg, M.; Oikonomou, K.; Schmid, C.; Rupprecht, L. (The Thoracic and Cardiovascular Surgeon, 2022)
Objectives Type A aortic dissection with true lumen collapse and malperfusion downstream is associated with a devastating prognosis. This study compares the clinical outcomes of two operative strategies for this disease: hybrid approach of ascending aorta (and hemiarch replacement) supplemented with retrograde stenting of the descending aorta (thoracic endovascular aortic repair [TEVAR]) and standard ascending aorta (and hemiarch) replacement without stent placement.Methods From January 1, 2016 to December 31, 2019, 81 patients with type A aortic dissection were studied. The hybrid technique was applied in 30 patients (group 1), while 51 patients received standard surgical repair (group 2). Patient demographics, clinical and operative findings, postoperative outcome, follow-up interventions, and mid-term survival were analyzed.Results Baseline characteristics were similar among the groups, except that more preoperative malperfusion was evident in group 1. The postoperative incidence of visceral malperfusion (0 vs. 15.7%, p = 0.02) and low cardiac output syndrome requiring extracorporeal membrane oxygenation support (3.3 vs. 19.6%, p = 0.04) was significantly less in group 1. In-hospital mortality was also significantly lower in group 1 as in group 2 (13.3 vs. 33.3%, p = 0.04). At follow-up, the need for secondary endovascular stenting (3.3 vs. 7.8%, p = 0.65) and surgical aortic reintervention (6.7 vs. 2.0%, p = 0.55) was comparable. One-year, 2-year, and 3-year survival rates were 83.3, 83.3, and 62.5% in group 1, and 58.7, 58.7, and 52.6% in group 2 (p = 0.05), respectively.Conclusion The combination of open surgical replacement of the ascending aorta (and hemiarch) with TEVAR of the descending aorta for true lumen compromise is a feasible treatment option for patients with type A aortic dissection and is associated with a better perioperative outcome and improved mid-term survival rate.
Keywords: type A aortic dissection; true lumen occlusion; TEVAR